Synthesis and properties of bromide‐ functionalized poly(isobutylene‐co‐p‐ methylstyrene) random copolymer. Issue 3 (7th December 2016) - Xie, Yi; Chang, Jin‐jie; Wu, Yi‐bo; Yang, Dan; Wang, Hao; Zhang, Tao; Li, Shu‐xin; Guo, Wen‐li
Abstract: Poly(isobutylene‐ co‐p ‐methylstyrene) (IB/ p ‐MS) random copolymer is a new generation of polyisobutylene‐based elastomers. The cationic copolymerization of IB with p ‐MS was thoroughly examined by using 2‐chloro‐2, 4, 4‐trimethylpentane/ethylaluminiumsesquichloride/electron donor as initiating system. IB/ p ‐MS random copolymers with high molecular weight were obtained at elevated temperature through the addition of ethyl acetate; the reaction proceeded in a mildly exothermic manner. Although the reactivity ratios of comonomer pairs differ by close to an order of magnitude, p ‐MS was uniformly distributed in the chains. IB/ p ‐MS random copolymer can be brominated by adding molecular bromine into the copolymer solution, thereby yielding a completely saturated polymer backbone with a chemically reactive site. The types and selection of appropriate vulcanization systems for bromide‐functionalized IB/ p ‐MS random copolymers are also discussed. © 2016 Society of Chemical Industry Synthesis and properties of bromide‐functionalized poly (isobutylene‐ co‐p ‐methylstyrene) random copolymer: Uniform IB/ p ‐MS random copolymers were successfully synthesized via a cationic copolymerization at elevated temperatures. The types and selection of appropriate vulcanization systems for bromide‐functionalized IB/ p ‐MS random copolymers are discussed.